Genetic evaluation of dystocia and its relationship with productive and reproductive traits in Holstein cows - Salimi, Mohammad Hossein; Ghavi Hossein-Zadeh, Navid; Shadparvar, Abdol Ahad; Eghbal, Ali Reza (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: dystocia is one of the most economically significant secondary traits in dairy cows and has adverse effects on the subsequent survival, health, and performance of mothers and offspring. Objective: the aim of this study was to estimate direct and maternal genetic parameters for calving ease (CE) and its relationship with productive and reproductive traits in Iranian Holstein cows. Methods: data from 1991 through 2011 were collected from the Animal Breeding Center of Iran, and contained 132,831 records of CE, 183,203 records of productive traits including 305-d adjusted milk yield (MY305), 305-d adjusted fat yield (FY305) and 305-d adjusted protein yield (PY305), and 129,199 records of reproductive traits including days open (DO), days to first service (DFS) and calving interval (CI). Univariate and bivariate linear animal models were used for the analysis of traits in two different models on which direct genetic effect (model 1) and direct + maternal genetic effects (model 2) using AI-REML algorithm were included. Results: estimated heritabilities for CE in model 1 were 0.02 in univariate and 0.02-0.03 in bivariate analyses. Direct and maternal heritabilities in model 2 were 0.02 and 0.002 for univariate, and 0.03 and 0.0004-0.006 in bivariate analyses, respectively. Genetic correlations between direct effects of CE with MY305, FY305, and PY305 were -0.99, 0.02 and -0.07 in model 1, and -0.2, -0.02 and -0.13 in model 2, respectively. Conclusion: this study suggested that a selection index that includes both direct and maternal effects should be included in CE breeding programs. , rendimiento productivo, aca lechera. Resumo Palavras chave: correlação genética, desempenho produtivo, dificuldade de parto, parâmetros genéticos, vaca de leiteria.